2019
DOI: 10.1111/cfs.12686
|View full text |Cite
|
Sign up to set email alerts
|

Age limits for participation in child protection court proceedings in Sweden

Abstract: According to the UN Convention on the Rights of the Child and Swedish legislation, children have the right to participate in child protection proceedings. The aim of this paper is to describe and analyse the notion of age and maturity in child protection proceedings in order to elucidate how these aspects could influence children's rights to participate. We focus on the view of three groups of actors involved in child protection proceedings in Sweden—social workers, lawyers, and laypersons in social welfare bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, partnership relations with parents are not uncontested, not to mention those with children (Calder 2008;Broadhurst 2010;Venables and Healey 2019;Hultman, Höjer, and Larsson 2019). Although the views of children and parents are not studied empirically in this paper, one may assume that for them the care order preparations can offer a platform of partnership, but also one of resignation, fight or escape (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, partnership relations with parents are not uncontested, not to mention those with children (Calder 2008;Broadhurst 2010;Venables and Healey 2019;Hultman, Höjer, and Larsson 2019). Although the views of children and parents are not studied empirically in this paper, one may assume that for them the care order preparations can offer a platform of partnership, but also one of resignation, fight or escape (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They may result in difficulties in, for example, communicating with children as service-users (e.g. Bijleveld et al, 2015;Handley & Doyle, 2014) or in assessing children's maturity for expressing consent (Hultman et al, 2019).…”
Section: The Notion Of Informed Consentmentioning
confidence: 99%
“…The theme of protectionism is discussed in numerous studies, indicating that workers tend to adopt a protective position with regard to children's participation (e.g. Alfandari, 2017;van Bijleveld et al, 2019;Collins, 2017;Hultman et al, 2019;Kosher & Ben-Arieh, 2019). Križ and Skivenes' (2017) study found that child welfare workers mentioned that children needed protection from possible harmful effects as a consequence of participation and that children do not always know what is in their best interest.…”
Section: First Are Children Competent Enough To Know What They Want Or?mentioning
confidence: 99%
“…Concerning participation, Križ and Skivenes (2017) highlight that Article 12 of the UNCRC grants children a prominent place in all matters that affect them. Hultman, Höjer, and Larsson (2019) refer to the Committee on the Rights of the Child (2009), which states that there should be no age limit, in law or in practice that would restrict a child's right to be heard in matters that impact them. Despite policy-makers, researchers and practitioners being increasingly focused on the participation of children in decision-making in the child protection system (Alfandari, 2017;van Bijleveld, Dedding, & Bunders-Aelen, 2015;Bouma, López López, Knorth, & Grietens, 2018;Franklin & Sloper, 2009;Hinton, Tisdall, Gallagher, & Elsley, 2008;Pålsson, 2017;Sanders & Mace, 2006), children's right to participation in decision-making remains challenging in practice (Kosher & Ben-Arieh, 2019;Mateos, Vaquero, Balsells, & Ponce, 2017;Ruiz-Casares, Collins, Tisdall, & Grover, 2017).…”
Section: Introductionmentioning
confidence: 99%